A method to manipulate non-steady-state columnar-to-equiaxed transition in powder bed fusion additive manufacturing using an electron beam - Lei, Yuchao; Aoyagi, Kenta; Chiba, Akihiko (Acta materialia, 2022)
Site-specific control of solidification grain structure is one of the largest attractiveness of manufacturing metallic parts with powder bed fusion additive manufacturing. In this study, we manufacture non-weldable superalloy Alloy713ELC with powder bed fusion additive manufacturing using an electron beam (PBF-EB) and achieve various bulk solidification grain structures, i.e. near fully equiaxed structure, interlocked zigzag structure, and columnar structures with various grain widths, through controlling process parameters under a line order scan strategy. An analytical transient model, which is capable of simulating heat transfer in PBF-EB single-layer melting under the experimental conditions, is established and validated by compared to numerical models of computational fluid dynamics and finite element method in PBF-EB single-track melting. The evolutions of solidification grain structure are rationalized using microstructural characterization and simulations based on various models. It is found that the mechanisms of columnar grain refinement and columnar-to-equiaxed transition (CET) are related to the Walton and Chalmers selection effect, which is governed by the spatial and temporal variations of solidification direction, and to the effect of convection within mushy zone. Based on the grain structure evolution mechanisms, we propose a method to manipulate CET or to achieve a novel interlocked zigzag grain structure in PBF-EB. [Display omitted] .